2021
DOI: 10.1111/bjh.17513
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns and outcomes of unfit and elderly patients with Mantle cell lymphoma unfit for standard immunochemotherapy: A UK and Ireland analysis

Abstract: Mantle cell lymphoma (MCL) presenting in elderly, unfit patients represents a clinical challenge. Front-line 'attenuated' or low-intensity immunochemotherapy is often employed, although outcomes are relatively unexplored. We report outcomes of attenuated immunochemotherapy in 95 patients with MCL across 19 centres in the UK and Ireland considered unfit for full-dose rituximab-bendamustine or rituximab-cyclophosphamide, doxorubicin, vincristine, prednisolone (R-CHOP). Regimens examined were rituximab-cyclophosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…Thus, although the data suggest that BR therapy was not inferior to R‐CHOP, it is important to take into consideration that this may not be the case because of the better demographics of the patients treated with BR. This is in line with a study completed in the United Kingdom after our data collection which found that the PFS of elderly/unfit patients treated in the United Kingdom with BR and R‐CHOP was not significantly different [ 72 ].…”
Section: Discussionsupporting
confidence: 90%
“…Thus, although the data suggest that BR therapy was not inferior to R‐CHOP, it is important to take into consideration that this may not be the case because of the better demographics of the patients treated with BR. This is in line with a study completed in the United Kingdom after our data collection which found that the PFS of elderly/unfit patients treated in the United Kingdom with BR and R‐CHOP was not significantly different [ 72 ].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, age (≥ 75 years) was a significant risk factor associated with failure of receiving subsequent therapy. Previous studies have reported similar findings [ 38 40 ], indicating a lack of effective therapy for this patient population. Other factors indicative of failure to receive post-ibrutinib therapy were emergency hospital admissions and poor ADL during ibrutinib therapy.…”
Section: Discussionsupporting
confidence: 71%
“…The standard frontline therapy for MCL is not completely uni ed, however, there is a general consensus that cytarabine-containing chemotherapy combined with autologous hematopoietic stem cell transplantation as the rst-line treatment for young and t patients, whereas older or un t patients are treated with combination chemo-immunotherapy according to different tolerance (9,(20)(21)(22)(23). Although the bene t of high-dose cytarabine is clear, due to different clinical trial results, the recognized uni ed regimen is not de nite.…”
Section: Discussionmentioning
confidence: 99%